2018
DOI: 10.1634/theoncologist.2017-0467
|View full text |Cite
|
Sign up to set email alerts
|

Mutant KRAS Circulating Tumor DNA Is an Accurate Tool for Pancreatic Cancer Monitoring

Abstract: Avoiding futile chemotherapy in metastatic pancreatic ductal adenocarcinoma (PDAC) patients by monitoring response to treatment is of utmost importance. A novel biomarker for monitoring treatment response in PDAC, using mutant circulating tumor DNA (ctDNA), is proposed. Results, although limited by small sample numbers, suggest that ctDNA can be an effective marker for disease monitoring and that ctDNA level over time is a better predictor of survival than the dynamics of the commonly used biomarker CA19-9. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
51
2
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 70 publications
(62 citation statements)
references
References 43 publications
6
51
2
2
Order By: Relevance
“…At baseline, there was no statistically significant relationship between CA19.9 and ctDNA ( n = 47; p = 0.170). Other studies have shown a correlation between CA19.9 and ctDNA, although the cohorts were of limited size . Surprisingly, we did not find ECOG status to be a significant prognosticator in the regression analysis.…”
Section: Discussioncontrasting
confidence: 94%
See 3 more Smart Citations
“…At baseline, there was no statistically significant relationship between CA19.9 and ctDNA ( n = 47; p = 0.170). Other studies have shown a correlation between CA19.9 and ctDNA, although the cohorts were of limited size . Surprisingly, we did not find ECOG status to be a significant prognosticator in the regression analysis.…”
Section: Discussioncontrasting
confidence: 94%
“…The prognostic value of ctDNA for OS ( p = 0.005) is in line with the results of a recent meta‐analysis of ctDNA in PDAC . In our study, ctDNA was an predictor of OS after adjustment for CA19.9 and treatment regimen, while CA19.9 was not an independent predictor after adjustment for ctDNA, an observation also reported by others . At baseline, there was no statistically significant relationship between CA19.9 and ctDNA ( n = 47; p = 0.170).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In metastatic PDAC, undetectable KRAS mutant ctDNA was significantly associated with survival benefit (8 months vs . 37.5 months, P < 0.004) (Perets et al ., ). For patients with resectable disease, MST of patients in whom ctDNA was detected were significantly shorter than those of patients in whom ctDNA was not detected (3.9 months vs .…”
Section: Clinical Application Of Ctdna In Pdacmentioning
confidence: 97%